How the interplay between individual spatial memory and landscape persistence can generate population distribution patterns - Berbert, Juliana M. [UNESP]; Fagan, William F. (Elsevier B.V., 2012)
Recent studies have suggested that the long distance movements of some terrestrial mammals are not migratory, but rather nomadic. Moreover, the spatial heterogeneity and temporal predictability of resources were proposed as factors contributing to alternative movement strategies, such as sedentarism (i.e., range residency), migration, and nomadism. Here, we propose that, at the individual level, a dependence on spatial memory is another important parameter for distinguishing among population-level patterns of spatial distribution. For instance, migratory animals would have a long memory of the areas they prefer to revisit, whereas nomadic animals would remember recently visited areas as places to avoid as they search for resources. We develop a computational model in which individuals movement decisions are based on the animals' spatial memory of previously visited areas. Through this approach, we delineate how the interplay between landscape persistence and spatial memory leads to sedentarism, migration, and nomadism. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Animal movement; Movement patterns; Foraging strategy; Partially self-avoiding walk; Migration; Nomadism